Optimalisasi Desain dan Komunikasi Pemasaran melalui Platform E-Commerce Produk Bawang Merah Varietas Rubaru sebagai Komoditi Unggulan Pertanian Sumenep - Kurli, Anis; Hidayat, Imam; Suharyanto, Deny Feri; Prayoga, Andika Priyas; Mubin, Alan Nuril; Putra, Deny Fardiansyah (Jurnal Pertanian Terpadu, 2025)
The lack of a unique design concept and effective marketing communication has made it difficult for processed agricultural products, specifically Rubaru variety shallots, to compete with other products. Local producers and entrepreneurs have yet to fully leverage packaging design as a branding tool through e-commerce platforms and social media. This study aims to optimize product design and marketing communication through a digital approach to enhance competitiveness and market reach. The research uses a qualitative exploratory method and applies a design thinking approach involving the stages of empathy, problem definition, ideation, prototyping, and testing. The findings indicate that the implementation of attractive packaging design, supported by storytelling-based marketing narratives and strategic optimization of e-commerce platforms, can significantly improve the visibility and consumer interest in Rubaru variety shallot products. The study concludes that the integration of visual communication design and digital marketing on e-commerce platforms is a key strategy in elevating the potential of processed agricultural commodities. This approach helps build a strong brand image, creates appealing and informative packaging, and fosters consumer trust in Rubaru variety shallot products in the modern market.